Handaxe and non‐handaxe assemblages during Marine Isotope Stage 11 in northern Europe: recent investigations at Barnham, Suffolk, UK. (November 2016) - Ashton, Nick; Lewis, Simon G.; Parfitt, Simon A.; Davis, Rob J.; Stringer, Chris
ABSTRACT: Britain has an important geological, environmental and archaeological record for Marine Isotope Stage 11 (MIS 11), which makes a major contribution to understanding of the human occupation of northern Europe. New fieldwork at Barnham, Suffolk, UK, has identified through improved geological resolution the change in assemblages from simple core and flake working to those with handaxe technology. The two assemblages are argued to reflect distinct human populations from different source areas in Europe. The paper examines the European record and puts forward a new model of how the complex mosaic of lithic assemblages reflects local, habitual practices during stable environments, but changes in climate and environment led to larger scale shifts in population, resulting in new human groups arriving in Britain.